AMIS Plus: Swiss registry of acute coronary syndrome. Issue 12 (10th June 2010) - Radovanovic, Dragana; Erne, Paul
Abstract : AIMS of AMIS Plus: To learn from each other, to understand the transfer, use and practicability of knowledge gained from randomised trials and to generate input for subsequent prospective and randomised studies. Furthermore, to determine how adherence to guideline-based treatments in the 'real world' works. Funding: AMIS Plus is an industry-sponsored project but the supporting institutions do not play any part in the design of the registry, data collection, analysis or interpretation. Quality-of-care interventions: AMIS Plus data enable doctors to identify deficits in medical care, implement the necessary changes in diagnostics and therapeutic procedures and document their impact on clinical outcome in patients with acute coronary syndrome (ACS). Setting: From 106 hospitals treating ACS in Switzerland, 76 hospitals temporarily or continuously enrolled patients in AMIS Plus. Years: 1997– Population: Patients are included on the basis of their final diagnosis. Current number of cases: 33 040. Start points: ST elevation myocardial infarction, non-ST elevation myocardial infarction and since 2000, unstable angina. Baseline data: 230 variables are collected including demographics, medical history, cardiovascular risk factors, acute symptoms, time of symptom onset, first medical contact, time of admission and start of thrombolysis or balloon, out of hospital management, clinical presentation, early in-hospital management, reperfusion treatment, hospital course, diagnostic tests used or planned, hospital length of stay, discharge medication, destination and at 1 year, outcome, rehospitalisation, intervention, working time and quality of daily life. Data capture: Data are provided through an internet- or paper-based questionnaire completed by the treating doctor or a trained study nurse. Data quality: The data are centralised at the AMIS Plus Data Center, checked for plausibility and consistency and crosschecked when queries arise. Incomplete questionnaires are returned to the enrolment centres for completion. One-third of the variables are obligatory. End point and linkages to other data: In-hospital outcome, 3-months and 1-year follow-up outcome. No linkages exist at present. Access to data: Available for research with the approval of the AMIS Plus Steering Committee. Participating hospitals use the data for benchmarking and their own quality control.